Covid-19 Impact on the Workers of the Informal Sector: A Longitudinal Study of Bangladesh - Firoj, Mahamuda; Khanom, Sharmina; Rashid, M Mamunur; Sultana, Abeda; Kallol, Humayun; Islam, Mohammed Nazrul; Sultana, Nair (Asian Development Policy Review, 2021)
The rapid spread of COVID-19 and subsequent restriction measures become a growing concern for its economic impacts as well. To address it, a study was undertaken to investigate the impacts upon the low-income people employed in the informal sectors in Bangladesh. The data of 372 respondents was collected through a structured questionnaire from the informal sectors in the cities of Dhaka and Chattogram, the most predominant hubs of the country’s informal workers. This study covered the period of the first wave of the pandemic in Bangladesh from its first detection (8 March 2020) to the onset of the second wave (February 2021). It was a little over the one year period that had been divided into four-time segments considering as before pandemic (January – March 2020), and during pandemic (1st quartile: April – July 2020; 2nd quartile: August – November 2020 and 3rd quartile: December 2020 - February 2021). In the 1st quartile during the pandemic, 65% of respondents' income revealed a sharp decline. This scenario continued in the 2nd and 3rd quartiles with the figure of 35% and 24% respectively. Thus, in each of the three quartiles during pandemic time slots, the majority of respondents' consumption, living standard, schooling, and access to health care facilities were found negatively impacted. By the continuity of time some of the respondents were able to settle them in the new socio-economic condition. Overall, these results indicated several recommendations, including extending basic assistance to these vulnerable groups.